Larger brains spur species diversification in birds. (1st October 2019) - Sayol, Ferran; Lapiedra, Oriol; Ducatez, Simon; Sol, Daniel
Abstract: Evidence is accumulating that species traits can spur their evolutionary diversification by influencing niche shifts, range expansions, and extinction risk. Previous work has shown that larger brains (relative to body size) facilitate niche shifts and range expansions by enhancing behavioral plasticity but whether larger brains also promote evolutionary diversification is currently backed by insufficient evidence. We addressed this gap by combining a brain size dataset for >1900 avian species worldwide with estimates of diversification rates based on two conceptually different phylogenetic‐based approaches. We found consistent evidence that lineages with larger brains (relative to body size) have diversified faster than lineages with relatively smaller brains. The best supported trait‐dependent model suggests that brain size primarily affects diversification rates by increasing speciation rather than decreasing extinction rates. In addition, we found that the effect of relatively brain size on species‐level diversification rate is additive to the effect of other intrinsic and extrinsic factors. Altogether, our results highlight the importance of brain size as an important factor in evolution and reinforce the view that intrinsic features of species have the potential to influence the pace of evolution.